On Topological Structures of Fuzzy Parametrized Soft Sets - Serkan Atmaca; İdris Zorlutuna (The Scientific World Journal)
We introduce the topological structure of fuzzy parametrized soft sets and fuzzy parametrized soft mappings. We define the notion of quasi-coincidence for fuzzy parametrized soft sets and investigated its basic properties. We study the closure, interior, base, continuity, and compactness and properties of these concepts in fuzzy parametrized soft topological spaces.